2017
DOI: 10.3390/su9101880
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and Polycentricity: Spatial Changes of Employment in Beijing Metropolitan Area, China

Abstract: Decentralization and polycentric spatial structure strategies are important ways to alleviate urban disease in China. However, whether the urban spatial structure is meeting expectations is still unknown. Taking the Beijing Metropolitan Area as a case, the author adopted a non-parametric method to identify the subcenters, then an employment density model was used to analyze the spatial changes of employment and the employment centers' impacts on the urban spatial structure. The results show that the Beijing Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Our results show that the standard deviation of the curvature in the landform is statistically nonsignificant, differing from previous studies (Liu and Wang 2016). The study area can influence the results of the identified subcenters (Lv et al 2017). PLACMDs, which are much smaller than Chinese cities at the prefectural level and above, are used as the study area in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that the standard deviation of the curvature in the landform is statistically nonsignificant, differing from previous studies (Liu and Wang 2016). The study area can influence the results of the identified subcenters (Lv et al 2017). PLACMDs, which are much smaller than Chinese cities at the prefectural level and above, are used as the study area in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The compact development of city centers has economic and social advantages (He et al 2016; Kong et al 2016), but also produces major urban diseases, such as lower quality of life, environmental pollution, high housing prices, traffic jams, etc. (Kong et al 2016; Lv et al 2017; Wang and Kwan 2017; Zheng and Kahn 2017). Government officials and urban planners in the West are exerting efforts to establish a polycentric urban spatial structure because they believe that polycentricity could enhance their cities’ competitiveness and environmental sustainability (Parr 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019, 8, 283 2 of 20 gradually declined [12]. In efforts to address this problem, it has been shown that decentralization and the development of polycentric cities can effectively alleviate 'big city disease' [13]. Moreover, the production efficiency and annual average wage in polycentric areas are generally higher than those in monocentric areas [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies, mainly empirical studies examining population distribution and land prices [2][3][4][5][6][7][8][9], have investigated the polycentric spatial structure in China's mega cities, and a few studies have done this from the perspective of employment distribution [10][11][12]. These studies have demonstrated that many mega cities in China have been experiencing polycentric development resulting from the emergence of subcenters and the increasing intensity of development in the suburbs.…”
Section: Introductionmentioning
confidence: 99%